Country strong [videorecording (DVD)] - Feste, Shana, 1976-; Paltrow, Gwyneth, 1972-; McGraw, Tim; Hedlund, Garrett, 1985-; Meester, Leighton, 1986- (Sony Pictures Home Entertainment, 2011)
Soon after a rising young singer-songwriter gets involved with a fallen, emotionally unstable country star, the pair embark on a career resurrection tour steered by her husband/manager, that includes a beauty-queen-turned-singer. Between the concerts, romantic entanglements and old demons threaten to derail them all.